Shadow Elimination in Soccer Game Video using Background Subtraction and Sobel Operators - Najeeb, Huda Dheyauldeen; Ghani, Rana Fareed (Iraqi Journal of Science, 2020)
Object detection in real time is considered as a challenging problem. However, it is very important in a wide range of applications, especially in field of multimedia. The players and ball are the most important objects in soccer game videos and detecting them is a challenging task because of many difficulties, such as shadow and illumination, ball size, ball occluded by players or merged with lines, and similar appearance of players. To overcome these problems, we present a new system to detect the players and ball in real-time by using background subtraction and Sobel detection. The results were more accurate and approximately two times faster than those using only background subtraction.